CHANGES IN THE CONDITION OF PATIENTS WITH IDIOPATHIC ATRIAL FIBRILLATION AND HYPERTENSION AFTER RESTORATION OF SINUS RHYTHM (Modern American Journal of Medical and Health Sciences, 2025)
Atrial fibrillation (AF) is one of the most pressing problems in cardiology, due to the widespread prevalence of this arrhythmia [5] and the severity of complications associated with it, among which the most unfavorable are the development of strokes [8,11] and heart failure [1, 6].